The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0166952
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Paternal Smoking and Offspring Adiposity: Further Investigation of a Potential Intergenerational Effect Using the HUNT Study

Abstract: Recently it has been suggested that rearing conditions during preadolescence in one generation may affect health outcomes in subsequent generations. Such parental effects, potentially induced by epigenetic modifications in the germ line, have attracted considerable attention because of their implications for public health and social policies. Yet, to date, evidence in humans has been rare due to data limitations and much further investigation in large studies is required. The aim of this paper is to reproduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28]. Paternal programming has been likewise described in clinical observation studies [41, 42]. So far most of the animal studies dealing with paternal programming used paternal high-fat diet models prior to mating to investigate potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28]. Paternal programming has been likewise described in clinical observation studies [41, 42]. So far most of the animal studies dealing with paternal programming used paternal high-fat diet models prior to mating to investigate potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Observations from the Överkalix and ALSPAC cohorts showed that excess food supply and smoking during mid-childhood and pre-pubertal years were associated with metabolic and cardiovascular health, and risk of becoming obese in subsequent generation(s) [ 16 19 ]. These findings remain to be successfully replicated, and there exists a possibility of residual confounding due to unmeasured family factors, especially due to the social patterning and inequalities related to smoking behaviour [ 20 , 21 ]. However, other epidemiological studies have reported adverse offspring outcomes related to paternal exposures in pre-puberty/puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Children of smoking fathers were more likely to be overweight or obese at 5 years of age but not at 9 years in the Lifeways Cross‐generation Cohort study (Mejia‐Lancheros et al, ), and daughters whose fathers smoked during pregnancy were at higher risk of overweight and obesity in the study by Harris et al (), presumably due to secondhand smoke exposure of the mother. In contrast, a study specifically addressing the link between paternal early‐onset smoking and offspring BMI in the Nord‐Trøndelag Health (HUNT) cohort (Carslake, Pinger, Romundstad, and Davey Smith, ) did not find an association between paternal preadolescent smoking and sons' BMI yet reported a marginal relationship with daughters' BMI.…”
Section: Maternal Smoking and Offspring Overweight And Obesitymentioning
confidence: 94%